2004
DOI: 10.1016/j.jasms.2003.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of melphalan modified 2′-oligodeoxynucleotides by miniaturized LC-ES MS/MS

Abstract: In this study a miniaturized LC coupled to electrospray tandem mass spectrometry was used to analyze modifications originating from the interaction between the chemotherapeutic agent melphalan and 2Ј-oligodeoxynucleotides. Low energy CAD product ion spectra gave information about the specificity of melphalan alkylation with regard to certain DNA sequences. These data can be very useful to estimate the risk in the development of secondary leukaemia as a result of a melphalan cure. In the study of the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Apart from modified nucleobases, LC-ESI-MS also allows for the detection of sugar-phosphate adducts and modified ODNs that are not amenable to GC-MS analysis. [89][90][91] Owing to the highly acidic nature of the phosphate backbone, such analyses are commonly performed in the negative-ion mode. Moreover, the ability of ESI in producing multiply charged ions, in combination with improved mass range of modern mass analyzers, has facilitated the characterization of large analytes like ODNs.…”
Section: Gc-msmentioning
confidence: 99%
“…Apart from modified nucleobases, LC-ESI-MS also allows for the detection of sugar-phosphate adducts and modified ODNs that are not amenable to GC-MS analysis. [89][90][91] Owing to the highly acidic nature of the phosphate backbone, such analyses are commonly performed in the negative-ion mode. Moreover, the ability of ESI in producing multiply charged ions, in combination with improved mass range of modern mass analyzers, has facilitated the characterization of large analytes like ODNs.…”
Section: Gc-msmentioning
confidence: 99%
“…When coupled to separation techniques such as HPLC and CE, the MS technique is particularly advantageous in analyzing oligonucleotides and DNA adducts in complex mixtures. The procedure often starts with enzymatic digestion (typically DNase I or nuclease P1) to deoxynucleotides or deoxynucleosides prior to further analysis by MS. ,,, However, DNA sequence information is lost as the oligomers are cleaved to individual deoxynucleotides or deoxynucleosides. It has been observed that reaction of carcinogens with DNA often exhibits sequence selectivity, the recognition of which may be important in order to understand their mutagenic activities. Hence it is advantageous to be able to obtain the sequence information from the analysis. The ability of electrospray-MS to form multiply charged ions, in combination with improved mass range in modern instruments, has made possible the detection and structural elucidation of larger digested fragments.…”
mentioning
confidence: 99%
“…Niessen, 9 Andrews et al, 8 and Koc and Swenberg 11 have recently reviewed the analysis of DNA adducts by MS. Applications include quantitation of nucleobase adducts with ethylene oxide, 29 2-amino-3,4-dimethylimidazo[4,5-f]quinoxaline, 12 acetaldehyde, 13 ene, 14 urethane, 15 tamoxifen, 16 melphalan, 17 and heterocyclic aromatic amines. 7 DNA adducts formed by oxidative stress were identified using MRM.…”
mentioning
confidence: 99%